Evaluation of hydrazone and N-acylhydrazone derivatives of vitamin B6 and pyridine-4-carbaldehyde as potential drugs against Alzheimer’s disease - Marija Bartolić; Ana Matošević; Nikola Maraković; Valentina Bušić; Sunčica Roca; Dražen Vikić-Topić; Antonio Sabljić; Anita Bosak; Dajana Gašo-Sokač (Journal of Enzyme Inhibition and Medicinal Chemistry)
The growing prevalence of Alzheimer’s disease calls for a drug that can simultaneously act towards several targets involved in the pathophysiology of the disease. In our study, we evaluated the potential of hydrazone and N-acylhydrazone derivatives of vitamin B6 and pyridine-4-carbaldehyde to be used as multi-target directed ligands targeting cholinergic system by inhibiting acetyl- and butyrylcholinesterase, lowering the accumulation of β-amyloid plaques by inhibiting both the β-secretase activity and amyloid self-aggregation, and maintaining the biometal balance by chelating certain biometals. Our results showed that all of the tested hydrazones were potent inhibitors of human cholinesterases with inhibition constants (Ki) in micromolar range able to lower the activity of β-secretase, inhibit amyloid aggregation, chelate biometals and act as antioxidants. Also, most of them were estimated to be able to cross the blood–brain barrier by passive transport and to be absorbed in human intestines as well as with moderate metabolic stability in liver microsomes.